2018
DOI: 10.1063/1.5064434
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of response time in GAGG:Ce scintillation crystals by magnesium codoping

Abstract: Dynamics of the population of the excited Ce states responsible for the luminescence response time in Gd3Al2Ga3O12:Ce scintillating crystals is studied by revealing the dynamics of nonequilibrium carriers in the picosecond domain. Optical pump and probe technique exploiting selective excitation of structural units of the crystal and probing the induced absorption as a function of time and spectral position is exploited. A fast response within a few picoseconds due to the absorption by holes at Gd ions and by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Another work by Szczęśniak et al [51] found that 0.3-0.4% Ca 2+ shortened the decay time to~30 ns. Codoping Mg 2+ to Gd 3 Al 2 Ga 3 O 12 :Ce scintillating crystals also improved response time [52].…”
Section: Rare-earth Oxyorthosilicatesmentioning
confidence: 95%
“…Another work by Szczęśniak et al [51] found that 0.3-0.4% Ca 2+ shortened the decay time to~30 ns. Codoping Mg 2+ to Gd 3 Al 2 Ga 3 O 12 :Ce scintillating crystals also improved response time [52].…”
Section: Rare-earth Oxyorthosilicatesmentioning
confidence: 95%
“…6 shows the rise time defined as the time period between the moment corresponding to the peak TA and the moment corresponding to 5% of the peak value (indicated by crosses in the main figure) for all samples studied. The rise time decreases with increasing doping level from plate PL1 towards PL6 and is shorter than those observed in GAGG:Ce before 40 .…”
Section: Transient Absorption Measurementsmentioning
confidence: 59%
“…Please do not adjust margins Please do not adjust margins possibly to certain shallow traps to return back to cerium ion, see Ref. 40. This part of TA response is presented in Fig.…”
Section: Transient Absorption Measurementsmentioning
confidence: 86%
See 1 more Smart Citation
“…Prof. Williams' research group suggested exploiting this approach for the investigation of free carriers, excitons, self-trapped holes, and charge states of the activator ions in scintillators CsI:Tl, NaI:Tl, and SrI 2 . 7 Subsequently, the transient absorption in the pump and probe configuration is successfully exploited to study prospective scintillators and enabled studying self-trapped excitons and Ce excited states in LaBr 3 :Ce and CeBr 3 , 8,9 proving the importance of carrier trapping and the influence of aliovalent codoping on luminescence response time in GAGG:Ce [10][11][12] and LYSO:Ce, 13 showing the influence of composition on carrier trapping in Ce-doped perovskites YAP-LuAP, 14 studying the ultrafast response decay of a Ga-doped ZnO scintillator, 15 revealing the role of inter-and intra-configurational excitation relaxation at the Pr 3+ ion in LuAG:Pr 16 and the influence of the composition of a garnet-type matrix on the energy relaxation rates in multicomponent GYAGG:Ce. 17 Correlation between the results obtained by the TA and CTR techniques is observed in GAGG:Ce 11,12 and LYSO:Ce.…”
Section: Introductionmentioning
confidence: 99%